ESD. - Voldman, Steven H. (John Wiley & Sons, Ltd, 2015)
ESD: Circuits and Devices 2nd Edition provides a clear picture of layout and design of digital, analog, radio frequency (RF) and power applications for protection from electrostatic discharge (ESD), electrical overstress (EOS), and latchup phenomena from a generalist perspective and design synthesis practices providing optimum solutions in advanced technologies